Effect of Defect Geometry and Strain Rate on Mechanoelectrochemical Behavior of X100 Steel Pipelines - Muhammad Zacky Syah; Andoko Andoko; Riduwan Prasetya (International Journal of Recent Technology and Applied Science (IJORTAS), 2025)
Corrosion and mechanical issues in high-strength X100 steel pipelines present major difficulties for the safety and dependability of energy transport systems. This research investigates the joint impacts of defect shape and strain rate on stress distribution as well as electrochemical behavior through COMSOL Multiphysics simulations. Findings show that defects with elevated aspect ratios generate intense stress gradients, resulting in focused plastic deformation and the onset of cracks. Additionally, higher strain rates worsen stress concentration and speed up anodic and cathodic reactions, amplifying hydrogen embrittlement and the deterioration of materials. As time passes, the redistribution of stress due to degradation leads to structural instability and increases the likelihood of failure. These results highlight the significance of combining mechanical and electrochemical analyses to gain a deeper insight into degradation mechanisms. This research offers important perspectives for enhancing defect surveillance, refining cathodic protection methods, and guaranteeing the enduring reliability of pipelines in dynamic and corrosive settings.